Older Age Increases the Amplitude of Muscle Stretch-Induced Cortical Beta-Band Suppression But Does not Affect Rebound Strength - Walker, Simon; Monto, Simo; Piirainen, Jarmo M.; Avela, Janne; Tarkka, Ina M.; Parviainen, Tiina M.; Piitulainen, Harri (Frontiers in Aging Neuroscience, 2020)
Healthy aging is associated with deterioration of the sensorimotor system, which impairs e.g. balance and somatosensation. However, the exact age-related changes in cortical processing of sensorimotor integration are unclear. This study investigated primary sensorimotor cortex (SM1) oscillations in the 15–30 Hz beta band at rest and following (involuntary) rapid stretches to the triceps surae muscles (i.e. proprioceptive stimulation) of young and older adults. A custom-built, magnetoencephalography (MEG)-compatible device was used to deliver rapid (190°·s-1) ankle rotations as subjects sat passively in a magnetically-shielded room while MEG recorded cortical signals. Eleven young (age 25±3 y) and 12 older (age 70±3 y) adults matched for physical activity level demonstrated clear 15–30 Hz beta band suppression and rebound in response to the stretches. A sub-sample (10 young and 9 older) were tested for dynamic balance control on a sliding platform. Older adults had greater cortical beta power pre-stretch (e.g. right leg: 4.0±1.6 fT vs. 5.6±1.7 fT, P=0.044) and subsequently greater normalized movement-related cortical beta suppression post-proprioceptive stimulation (e.g. right leg: -5.8±1.3 vs. -7.6±1.7, P=0.01) than young adults. Furthermore, poorer balance was associated with stronger cortical beta suppression following proprioceptive stimulation (r = -0.478, P = 0.038, n = 19). These results provide further support that cortical processing of proprioception is hindered in older adults, potentially (adversely) influencing sensorimotor integration. This was demonstrated by impairment of prompt motor action control, i.e. regaining perturbed balance. Finally, SM1 cortex beta suppression to a proprioceptive stimulus seems to indicate poorer sensorimotor functioning in older adults.